Low back pain among office workers in three Spanish-speaking countries: Findings from the CUPID study - Campos-Fumero, Adriana; Delclos, George; Douphrate, David; Felknor, Sarah; Vargas-Prada, Sergio; Serra, Consol; Coggon, David; Ruiz- De Porras, David Gimeno (Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Seguridad Laboral, 2017)
Objectives—To assess differences in the prevalence and incidence of low back pain (LBP) and associated disability among office workers in Costa Rica, Nicaragua and Spain. Methods—Data were collected at baseline (n=947, 93% response) in November 2007 and at follow-up after 12 months (n=853, 90% response). Six outcome measures were examined: baseline prevalence of (1) LBP in past 12 months, (2) LBP in past month, and (3) disabling LBP in past month; and at follow-up: (4) incidence of new LBP in the past month, (5) new disabling LBP, and (6) persistent LBP. Differences in prevalence by country were characterized by odd ratios (ORs) with 95% confidence intervals (95%CIs), before and after adjustment for covariates. Results—Prevalence of LBP in the past month among office employees in Costa Rica (46.0%) and Nicaragua (44.2%) was higher than in Spain (33.6%). Incidence of new LBP was 37.0% in Nicaragua (OR=2.49; 95% CI: 1.57-3.95), 14.9% in Costa Rica (OR=0.74; 95% CI: 0.41-1.34), and 19.0% in Spain (reference). Incidence of new disabling LBP was higher in Nicaragua, 17.2%(OR=2.49; 95% CI: 1.43-4.34) and Costa Rica, 13.6% (OR=1.89; 95% CI: 1.03-3.48) than Spain (7.7%), while persistence of LBP was higher only in Nicaragua. Conclusions—Prevalence of LBP and disabling LBP was higher in Costa Rican and Nicaraguan office workers than in Spain, but incidence was higher mainly in Nicaragua. Measured sociodemographic, job-related and health-related variables only partly explained the differences between countries, and further research is needed to explore reasons for the remaining differences.
Artículo científico
Keywords: Estudios; Dolores; Músculos; Factores de riesgo; Research Subject Categories::MEDICINE::Social medicine::Public health medicine research areas::Occupational medicine